2017
DOI: 10.1007/s00170-017-0481-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterisation and modelling of rheokinetic properties of different silicone elastomers

Abstract: Elastomer injection moulding is a process whereby an elastomer mix is injected into a closed mould where the material is shaped to the desired geometry. Once completely filled, the silicone elastomer mix is vulcanised. Vulcanisation is the process whereby a viscous flow of silicone is converted into an elastic material through the incorporation of chemical cross-links between the material chains. To correctly use simulation tools to predict the filling of die mould cavities, it is necessary to characterise the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The curing process is based on chemical reaction kinetics. The vulcanization time of an LSR has a significant impact on molding product of a convex lens because the vulcanization is a crucial step in LSR injection molding [ 21 , 22 , 23 ]. Generally, both CHCs and CCCs are a complex heat transfer problem with transient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The curing process is based on chemical reaction kinetics. The vulcanization time of an LSR has a significant impact on molding product of a convex lens because the vulcanization is a crucial step in LSR injection molding [ 21 , 22 , 23 ]. Generally, both CHCs and CCCs are a complex heat transfer problem with transient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, a rheometer may be used by assuming the degree of cure is proportional to the change in viscosity. [ 108 ] These data may then be fit to the various models. [ 39,80,97,78,104,100,109,64 ]…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…It was found that the simulation results fit the shear viscosity behaviors of silicone LSR4350 well and the proposed Isayev-Deng model fits the curing kinetic reaction of elastomer materials well. Ou et al [ 18 ] developed mathematical models for the thermo-kinetic parameters of silicone elastomers.…”
Section: Introductionmentioning
confidence: 99%